2022
DOI: 10.1002/advs.202204178
|View full text |Cite
|
Sign up to set email alerts
|

Organism‐Generated Biological Vesicles In Situ: An Emerging Drug Delivery Strategy

Abstract: Biological vesicles, containing genetic materials and proteins of the original cells, are usually used for local or systemic communications among cells. Currently, studies on biological vesicles as therapeutic strategies or drug delivery carriers mainly focus on exogenously generated biological vesicles. However, the limitations of yield and purity caused by the complex purification process still hinder their clinical transformation. Recently, it has been reported that living organisms, including cells and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Reduction of renal blood flow is considered to be one of important pathogenic steps in the development of AKI, which usually results in decreased kidney perfusion. If reduced renal blood flow is reversed rapidly, the kidney is less prone to injury, including structural (acute tubular necrosis) and functional (proteinuria) damages 50 - 52 . Here, we report that the renal tubule specific knockout of ELA reduces renal blood flow and aggravates tubular injury (Figure 4 ) under the injury, while administration of ELA peptide increases renal blood flow and relieves tubular damage (Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of renal blood flow is considered to be one of important pathogenic steps in the development of AKI, which usually results in decreased kidney perfusion. If reduced renal blood flow is reversed rapidly, the kidney is less prone to injury, including structural (acute tubular necrosis) and functional (proteinuria) damages 50 - 52 . Here, we report that the renal tubule specific knockout of ELA reduces renal blood flow and aggravates tubular injury (Figure 4 ) under the injury, while administration of ELA peptide increases renal blood flow and relieves tubular damage (Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…(5) The risk of altering the orientation of membrane proteins when performing membrane-disrupting manipulations such as drug delivery to exosomes, which may result in recognition by the immune system and subsequent adverse reactions. Recently, in situ exosome-based drug delivery strategies based on organism generation have provided researchers with a new idea, which involves transforming in vitro isolation, drug loading, and modified delivery into in situ release at the lesion site, thus avoiding the risk of altering exosome properties and characteristics [ 222 ]. (6) Criteria for manufacturing, loading efficiency, purification, storage, use, stability duration, dose, and application are yet to be determined [ 223 ].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…For instance, it has been shown that due to the presence of CD47 on the surface of exosomes, phagocytosis by circulating monocytes can be efficiently avoided, thus promoting the metastasis of cargo. Therefore, using exosomes as carriers and modifying them for clinical applications by artificially optimizing the integration of specific loads such as tumor drugs and targeted siR-NAs is a promising and inspiring idea [99,100]. This denotes that exosome-based therapies are emerging cutting-edge strategies to inhibit tumor progression.…”
Section: Macrophage-derived Exosomes For Cancer Therapymentioning
confidence: 99%